(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
In the United States, especially at the state level, the unborn child has already been widely acknowledged as human being overcoming the so called “born alive rule”. A line of demarcation is that in which the recognition of the human being to be born as a “person” contrasts with the protection of the fundamental rights of the mother. This debate has been fired up by Dobbs case.